Deep brain reorienting : understanding the neuroscience of trauma, attachment wounding, and DBR psychotherapy - Corrigan, Frank M.; Young, Hannah; Christie-Sands, Jessica (New York, NY : Routledge, 2025)
"Deep Brain Reorienting introduces a novel, evidence-based approach to the treatment of trauma-related disorders. Steeped in neuroscience, this book builds on recent scientific contributions to the effects of shock, trauma, and neglect on the brain at the deepest levels. Enhanced by detailed case material and underpinned by a strong theoretical framework, the authors give special attention to clinically significant forms of dissociation, as well as attachment wounding and its treatment. This neurobiologically informed focus offers fresh perspectives, reaching beneath the level of cognitive, affective and defensive components of traumatic responding. Written at the interface of neuroscience and psychotherapy, this book will be invaluable to psychotherapists whose clinical practice is calling for new ways to work with the effects of traumatic experiences. In addition, several hypotheses will appeal to research-oriented psychotherapists and clinically led researchers in a range of fields"--
Keywords: Psychic trauma -- Treatment; Dissociative disorders -- Treatment; Brain -- Pathophysiology; Dissaco; Neurosciences; PSYCHOLOGY / Psychopathology / Post-Traumatic Stress Disorder (PTSD)